Validity and efficacy of the labor contract - Toyama, Jorge (2012)
The validity and efficacy of the labor contract as well as cases of nullity and defeasibility import an analysis of scopes of the supplementary application of Civil Code taking into account the peculiarities of Labor Law. Labor contract, while legal business has as regulatory framework to the regulations of Civil Code but it is necessary to determine, in each case, whether to apply fully this normative body, or modulate its supplemental application, or simply conclude that it doesn’t result compatible its regulation due to the special nature of labor relations. Specifically, this issue will be analyzed from cases of nullity and defeasibility of the labor contract.